Attitude towards Telemonitoring in Orthodontists and Orthodontic Patients - Domenico Dalessandri; Linda Sangalli; Ingrid Tonni; Laura Laffranchi; Stefano Bonetti; Luca Visconti; Alberto Signoroni; Corrado Paganelli (MDPI AG, 2021)
The purpose of this study was to analyze the attitude of dentists and patients towards the use of Dental MonitoringTM (DM), an orthodontic telemonitoring software. Thus, two different specially prepared specific questionnaires were administered to 80 dentists (40 were general dentists and 40 orthodontists) and 80 orthodontic patients. All dentists judged positively telemonitoring, as 96.25% of them considered telemonitoring indicative of high tech and high-quality treatment; 100% considered it a way to reduce the number of in-office visits; 17.5% agreed on a weekly telemonitoring frequency, 40% on a biweekly, and 42.5% on a lower frequency. Further, 97.5% of patients judged positively telemonitoring; 81.25% of them considered telemonitoring indicative of high-tech treatment; 81.25% declared to be interested in reducing the number of in-office visits through telemonitoring; 27.5% agreed on taking self-picture every week, 57.5% every two weeks, and 15% on a lower frequency. Both patients and dentists positively judged telemonitoring, considering it a technologically advanced tool increasing the perception of quality and accuracy of the treatment. Both groups were interested in reducing the number of in-office visits, although not all of them revealed to be ready to invest more money and time in it.